Polıtıcal busıness cycles ın the Turkısh economy: 1977-2001 - Gezgin, Yasemin (My University, 2014)
This study is about political business cycles (PBC) and investigates the Turkish case in the 1977-2001 period. The PBC literature has been developed in the last four-five decades and links economics and politics in several ways. In the first part of the study, developments in the literature are mentioned and the link between New Classical Economics and New Political Economics is introduced. In the second part, Turkish case is analyzed in details to determine whether there have been PBC during the above mentioned period. The results show that there have been political cycles in some macroeconomic variables which are currency issued, broad money (M1), public sector credits and agricultural credits extended by Central Bank of the Republic of Turkey (CBRT), and tax revenues. CBRT has not allowed PBC especially on the targeted variables (CBRT balance sheet size, net domestic assets and monetary base), after 1989. Due to the high legal ceilings of CBRT credits to the public sector, CBRT was not able to limit those credits, especially before 1991 general elections. There had been similar PBC on agricultural credits which had been extended in the 1977-1991 period by CBRT. In addition to the regression analysis, comparative tables and figures for personnel expenditures of State Economic Enterprises (SEEs), agricultural credits which had been extended by Agricultural Bank of the Republic of Turkey (ABRT) in the 1964-1998 period and agricultural prices which had been declared by governments in the 1986-1999 period are provided in the paper. The study provides some evidence to PBC literature and determines which policy instruments could have been used to produce PBC in the Turkish economy. And it is also important to learn which policies can be manipulated in order to prevent the PBC in the future.
Keywords: Political business cycles; Autoregression analysis; Time series analysis; Structural breaks; Dummy variables; Turkish economy.